Liver Ultrasound Patterns in Children With Cystic Fibrosis Correlate With Noninvasive Tests of Liver Disease. Issue 3 (September 2019) - Ling, Simon C.; Ye, Wen; Leung, Daniel H.; Navarro, Oscar M.; Weymann, Alexander; Karnsakul, Wikrom; Freeman, A. Jay; Magee, John C.; Narkewicz, Michael R.
ABSTRACT: Objectives: Early identification of children with cystic fibrosis (CF) at risk for severe liver disease (CFLD) would enable targeted study of preventative therapies. There is no gold standard test for CFLD. Ultrasonography (US) is used to identify CFLD, but with concerns for its diagnostic accuracy. We aim to determine if differences in standard blood tests, imaging variables and noninvasive liver fibrosis indices correlate with liver US patterns, and thus provide supportive evidence that a heterogeneous US liver pattern reflects clinically relevant liver disease. Methods: We studied baseline research abdominal US and bloodwork from 244 children with pancreatic insufficient CF, ages 3 to 12 years, enrolled in a prospective study of the ability of US to predict CF cirrhosis (PUSH study). Children with a heterogeneous (HTG) liver pattern on US (n = 62) were matched 1 : 2 in design with children with normal US (NL, n = 122). Analyses included children with nodular (NOD, n = 22) and homogeneous hyperechoic (HMG, n = 38) livers. Results: Univariate analysis showed significant differences between US groups for standard blood tests, spleen size, and noninvasive liver fibrosis indices. Multivariable models discriminated NOD versus NL with excellent accuracy (AUROC 0.96). Models also distinguish HTG versus NL (AUROC 0.76), NOD versus HTG (0.78), and HMG versus NL (0.79). Conclusions: Liver US patterns in children with CF correlate with platelet count, spleen size and indices of liver fibrosis. Multivariable models of these biomarkers have excellent discriminating ability for NL versus NOD, and good ability to distinguish other US patterns, suggesting that US patterns correlate with clinically relevant liver disease. Abstract : Supplemental Digital Content is available in the text